Expanding English Vocabulary Knowledge through Reading: Insights from Eye-tracking Studies. (April 2020) - Pellicer-Sánchez, Ana
Students in academic contexts are expected to engage with large amounts of reading and they frequently meet unknown words and phrases in those reading materials. Previous research has shown that second and foreign language learners can acquire some of the unknown vocabulary that they encounter during reading. However, these previous findings were mainly based on scores in off-line, post-reading tests and thus, our understanding of the cognitive processes involved during learning from reading has been rather limited. Technological advancements have made it easier for researchers to explore learners' online processing behaviour. One of such advancements is eye-tracking, which provides a rich record of online reading behaviour. The last decade has witnessed an unprecedented increase in the number of eye-tracking studies conducted in second/foreign language learning research, with a particular focus on vocabulary learning from reading. This article illustrates how the use of eye-tracking has helped researchers gain a better understanding of the process of vocabulary learning from reading and of the relationship between eye-movements and performance measures. This article discusses recent research findings and identifies directions for future research.